Cura, relazione, professione: questioni di genere nel servizio sociale Il contributo italiano al dibattito internazionale - Di Rosa, Roberta T.; Luigi, Gui (Condivisione del sapere nel servizio sociale, 2022)
The persistence of a separation in work roles and tasks between men and women, which reproduces the partition between the private sphere, linked to the feminine, and the public sphere, unbalanced on the masculine, is particularly evident in the social, health and educational professions even in the most economically advanced countries, regardless of the welfare structures. Starting from the unequivocal evidence of the numerical prevalence of women in social work - a feature common to all the different conjugations in which the profession is expressed from State to State - the authors discuss the issue of gender in social work from different angles, offering the reader a rich plurality of themes, theoretical concepts and research approaches. National and international researches show the persistence of cultural matrices and gender stereotypes with regard to the division of labour, noticeable already during training, in the mentality of students and trainers, and often also in professionals themselves. The critical reflections of the authors are oriented towards the search for an antidote to the permanence of the status quo, and at the same time towards the development of an advanced mode of social intervention and gender-aware attention, both among professionals and with users and clients of the services. These research paths are offered as a contribution towards developments of a different kind in the multiple fronts of training (university education and lifelong learning), collective and mass media narration, research and reflexivity produced by the professional community of social workers themselves.